2013
DOI: 10.1002/jobm.201200564
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of siderophore producing antagonistic rhizobacteria against Rhizoctonia solani

Abstract: Plant protection through siderophore producing rhizobacteria (SPR) has emerged as a sustainable approach for crop health management. In present study, 220 bacteria isolated from tomato rhizosphere were screened for in vitro antagonistic activity against Rhizoctonia solani AG-4. Nine potent antagonistic strains viz., Alcaligenes sp. (MUN1, MB21, and MPF37), Enterobacter sp. (MPM1), Pseudomonas sp. (M10A and MB65), P. aeruginosa (MPF14 and MB123) and P. fluorescens (MPF47) were identified on the basis of physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 42 publications
4
47
0
1
Order By: Relevance
“…The identity of the BCA (isolate #7) was further confirmed by the ribosomal gene (16 S rRNA) sequence analysis, and the isolate revealed 100% sequence similarity with S. globosus (Krassilnikov, 1941) Waksman in Waksman and Lechevalier (1953) and Streptomyces toxytricini (Preobrazhenskaya and Sveshnikova, 1957; Pridham et al, 1958). The 16 S rRNA sequencing has been used as a basic approach for the identification of microbial communities as well as for assessing microbial diversity in natural environments (Solanki et al, 2014). Based on morphological, cultural and physiological characterizations, our results confirmed that the selected species was S. globosus (Strain UAE1).…”
Section: Discussionmentioning
confidence: 99%
“…The identity of the BCA (isolate #7) was further confirmed by the ribosomal gene (16 S rRNA) sequence analysis, and the isolate revealed 100% sequence similarity with S. globosus (Krassilnikov, 1941) Waksman in Waksman and Lechevalier (1953) and Streptomyces toxytricini (Preobrazhenskaya and Sveshnikova, 1957; Pridham et al, 1958). The 16 S rRNA sequencing has been used as a basic approach for the identification of microbial communities as well as for assessing microbial diversity in natural environments (Solanki et al, 2014). Based on morphological, cultural and physiological characterizations, our results confirmed that the selected species was S. globosus (Strain UAE1).…”
Section: Discussionmentioning
confidence: 99%
“…Disease sick plots were artificially prepared by mixing actively grown wheat bran culture of R. solani in natural soil according to Solanki et al . . Seedlings were treated with antagonistic bacterial strains as described in pot experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Field plots (3 Â 3 m 2 ) comprised five rows and five plants row À1 laid in a randomized block design with five treatments: T1-MB14 (10 À8 cfu ml À1 ), T2-MB101 (10 À8 cfu ml À1 ), T3-Carbendazim 50 wettable powder (0.1%), T4-healthy control (without pathogen and antagonist) and T5-R. solani infested control. Disease sick plots were artificially prepared by mixing actively grown wheat bran culture of R. solani in natural soil according to Solanki et al [2]. Seedlings were treated with antagonistic bacterial strains as described in pot experiment.…”
Section: Field Evaluationmentioning
confidence: 99%
“…Chemical and cultural control are the most common management techniques (Beebe et al, 1991;Godoy-Lutz et al, 1996a;Polanco et al, 1996), but during the last decades the biocontrol using different bacterial genus has been adopted as a sustainable approach for crop health management. However, they are not sufficient to avoid production losses (Solanki et al, 2013;Kanini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%